Evaluation of the Alpha-Fetoprotein Model for Predicting Recurrence and Survival in Patients With Hepatitis B Virus (HBV)–Related Cirrhosis Who Received Liver Transplantation for Hepatocellular Carcinoma - Ren, Ao; Li, Zhongqiu; Zhou, Xiaozhuan; Zhang, Xuzhi; Huang, Xiaochun; Deng, Ronghai; Ma, Yi (Frontiers in Surgery, 2020)
Introduction: The alpha-fetoprotein (AFP) model is superior to the Milan criteria in predicting the recurrence of hepatocellular carcinoma (HCC) after liver transplantation in European and Latin American populations. The purpose of this study was to determine the predictive value of the AFP model in Chinese hepatitis B virus (HBV)–related cirrhosis HCC patients. Methods: A total of 189 patients with HBV-related cirrhotic HCC were included. The recurrence rate and survival rate were estimated, and predictability was assessed by the Net Reclassification Improvement (NRI) method. Results: Of the 189 patients, patients with an AFP score >2 had a higher recurrence rate at 5 years (48.94 vs. 13.53%, p < 0.05) and lower survival rate (43.96 vs. 68.97%, p < 0.05). Considering patients within the Milan criteria, a higher 5-year recurrence rate and lower survival rate were observed in patients with an AFP model score >2 points compared to patients with a score of ≤ 2 points (recurrence rate: 58.75 vs. 12.98%, p < 0.05; survival rate: 28.57 vs. 67.41%, p = 0.047). NRI analysis showed that the AFP model exhibited superior predictability as compared to the Milan criteria. Conclusions: The AFP model may be used as a selection tool for Chinese HBV patients who require liver transplantation due to HCC.